Romanticisme of the forest Ukraine in the assessment of D. Chuzhevsky - Гаєвська, Н.; Наумовська, О. (Київський національний університет імені Тараса Шевченка, 2021)
The article focuses on D. Chyzhevsky's assessment of Lesya Ukrainka's romanticism, outlines the latest trends in the literature of the late XIX – early XX centuries, which professed Lesya Ukrainka as a neo-romantic. The aesthetics of romanticism and its transformation into neo-romanticism are traced. It is about identifying and analyzing the symbolism of Lesya Ukrainka's works. The subject matter of the poet's works is considered, the influence of romantic ideas (German, Polish romanticism) at the end of the XIX century is comprehended; combination of theoretical views of the writer with works of art, which is characteristic of romantic writers.

Акцентовано увагу на оцінці Д. Чижевським романтизму Лесі Українки, окреслено новітні тенденції в літературі кінця ХІХ – початку ХХ ст., які сповідувала Леся Українка як неоромантик. Досліджено естетику романтизму та його трансформацію в неоромантизм, зокрема виявлено і проаналізовано символіку творів Лесі Українки. Розглянуто тематику творів поетки, осмислено вплив романтичних ідей (німецького, польського романтизму) у кінці ХІХ ст.; поєднання теоретичних поглядів письменниці з художніми творами, що є характерним для письменників-романтиків.
Романтизм Лесі Українки в оцінці Д. Чижевського
Keywords: romanticism; literary process; symbolism; theater; tendencies; conventionality; романтизм; літературний процес; символічність; театр; тенденції; умовність